The New York State SARS-CoV-2 Testing Consortium: Regional Communication in Response to the COVID-19 Pandemic. (6th May 2021) - Crawford, James M.; Aguero-Rosenfeld, Maria E.; Aifantis, Ioannis; Cadoff, Evan M.; Cangiarella, Joan F.; Cordon-Cardo, Carlos; Cushing, Melissa; Firpo-Betancourt, Aldolfo; Fox, Amy S.; Furuya, Yoko; Hacking, Sean; Jhang, Jeffrey; et al.
The COVID-19 pandemic, caused by severe acute respiratory syndrome coronavirus 2, created an unprecedented need for comprehensive laboratory testing of populations, in order to meet the needs of medical practice and to guide the management and functioning of our society. With the greater New York metropolitan area as an epicenter of this pandemic beginning in March 2020, a consortium of laboratory leaders from the assembled New York academic medical institutions was formed to help identify and solve the challenges of deploying testing. This report brings forward the experience of this consortium, based on the real-world challenges which we encountered in testing patients and in supporting the recovery effort to reestablish the health care workplace. In coordination with the Greater New York Hospital Association and with the public health laboratory of New York State, this consortium communicated with state leadership to help inform public decision-making addressing the crisis. Through the length of the pandemic, the consortium has been a critical mechanism for sharing experience and best practices in dealing with issues including the following: instrument platforms, sample sources, test performance, pre- and post-analytical issues, supply chain, institutional testing capacity, pooled testing, biospecimen science, and research. The consortium also has been a mechanism for staying abreast of state and municipal policies and initiatives, and their impact on institutional and laboratory operations. The experience of this consortium may be of value to current and future laboratory professionals and policy-makers alike, in dealing with major events that impact regional laboratory services.